1999
DOI: 10.1046/j.1440-1681.1999.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVATION OF VASCULAR SMOOTH MUSCLE K+ CHANNELS BY ENDOTHELIUM‐DERIVED RELAXING FACTORS

Abstract: 1. Endothelium-derived relaxing factors (EDRF), including nitric oxide (NO), prostacyclin (PGI2) and an as yet uncharacterized endothelium-derived hyperpolarizing factor (EDHF), are now recognized to induce relaxation of vascular smooth muscle, in part via the activation of K+ channels. 2. Experiments using selective K+ channel blockers, including iberiotoxin (IbTX), glibenclamide, apamin and 4-aminopyridine (4-AP) to inhibit endothelium-induced relaxation suggest that more than one type of K+ channel may be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 36 publications
0
81
0
Order By: Relevance
“…34 Each of the endotheliumderived relaxing factors, namely NO, prostacyclin, and endothelium-derived hyperpolarizing factor, can activate one or several types of SMC K þ channels. 35 We detected three NOSs in our arterial data set, specifically the previously mentioned NOS1 (or nNOS), as well as NOS2 (or iNOS) and NOS3 (or eNOS).…”
Section: Cerebrovascular Proteomics a Badhwar Et Almentioning
confidence: 70%
“…34 Each of the endotheliumderived relaxing factors, namely NO, prostacyclin, and endothelium-derived hyperpolarizing factor, can activate one or several types of SMC K þ channels. 35 We detected three NOSs in our arterial data set, specifically the previously mentioned NOS1 (or nNOS), as well as NOS2 (or iNOS) and NOS3 (or eNOS).…”
Section: Cerebrovascular Proteomics a Badhwar Et Almentioning
confidence: 70%
“…Activation of PKA in vascular smooth muscle cells by an elevated cytoplasmic cAMP concentration results in relaxation as a result of phosphorylations both of effector proteins, including myosin light chain kinase, and of the ion channels that regulate the cytosolic Ca 2ϩ concentration and hyperpolarization (e.g., K ϩ channels) (41,52,58). Furthermore, PKA-mediated phosphorylations underpin the EDHF phenomenon in several arteries (21,56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it preserves endothelium-dependent relaxation and vascular contraction in STZ-induced diabetes, possibly by reducing iNOS expression in the aorta, by decreasing plasma levels of TNF- α and IL-6, and by preventing lipid peroxidation [52]. There is evidence that NO may increase activation of both the ATP-dependent K + -channel and the Ca 2+ -dependent K + -channel in vascular smooth muscle cells [53]. Similar experiment showed that procyanidins in Crataegus extract may be responsible for the endothelium-dependent NO-mediated relaxation, possibly via activation of tetraethylammonium sensitive K + channels in isolated rat aorta [54].…”
Section: Cardiovascular Effectmentioning
confidence: 99%